The professional training of public health doctors in Buenos Aires 1960-1970. A contribution from prosopography - Rayez, Federico Ramón (Universidad Pedagógica y Tecnológica de Colombia, 2021)
The article analyses the training and professional performance of the sanitarista doctors (public health doctors), health engineers, nurses and other agents who acted as teachers and researchers in the School of Public Health of the University of Buenos Aires between 1960-1970. To discover the main patterns of this social and scientific-professional experience, we propose to approach a set of trajectories from a method based on prosopography or collective biography. In this sense, the idea is, firstly, to analyse the problems, advantages and possible limits of these historical research methods, for which we took into consideration some relevant parameters and discussions that different authors, such as P. Bourdieu, L.Stone, S. Shapin, A. Thackray, L. Pyenson, among others, have proposed in the last decades. At a second stage, and based on an exhaustive review of autobiographical stories, personal records, and other administrative papers, a reconstruction was proposed of the professional trajectories of these experts in public health. This collective biographical analysis allows the identification of the patterns of academic circulation of these agents (their careers and universities of origin), work experience (their participation in the rgentine sanitary system of the mid-20th century), their transnational itineraries (formative trips, participation in professional consultancies, their bonds with inter-American organisms). As will be illustrated here, by focusing on an individual case or on multiple cases, the use of methods centred in the search of personal and biographical information is a useful tool in order to historicise complex processes and transformations in academic communities, which have not yet been studied in depth.